Implementasi Kebijakan Layanan Kunjungan Era New Normal Di Lembaga Pemasyarakatan Kelas II B Kayuagung - Apriansyah, Apriansyah; Novaria, Eva; Sandy, Amiruddin (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
This research aims to analyze the implementation of visiting service policies at the Class II B Kayuagung Correctional Institution during the New Normal era. This policy was implemented in response to the COVID-19 pandemic which required adjustments to visiting procedures to maintain the health and safety of inmates, staff and visitors. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation and document study. The research results show that the visiting service policy at the Class II B Kayuagung Prison includes several significant changes, such as limiting the number of visitors, implementing strict health protocols, and using technology for virtual visits. Although this policy aims to minimize the risk of spreading COVID-19, there are several challenges in its implementation, including limited infrastructure to support virtual visits and resistance from some visitors to new procedures.Further discussion reveals that the successful implementation of this policy is highly dependent on effective outreach, training for officers, as well as improving technological facilities. The conclusion of this research is that although the New Normal era visiting service policy at the Class II B Kayuagung Prison has made a positive contribution in preventing the spread of COVID-19, various efforts are still needed to overcome existing challenges to ensure the sustainability and effectiveness of this policy.